If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 14(p + 15) = 42(p + -5) Reorder the terms: 14(15 + p) = 42(p + -5) (15 * 14 + p * 14) = 42(p + -5) (210 + 14p) = 42(p + -5) Reorder the terms: 210 + 14p = 42(-5 + p) 210 + 14p = (-5 * 42 + p * 42) 210 + 14p = (-210 + 42p) Solving 210 + 14p = -210 + 42p Solving for variable 'p'. Move all terms containing p to the left, all other terms to the right. Add '-42p' to each side of the equation. 210 + 14p + -42p = -210 + 42p + -42p Combine like terms: 14p + -42p = -28p 210 + -28p = -210 + 42p + -42p Combine like terms: 42p + -42p = 0 210 + -28p = -210 + 0 210 + -28p = -210 Add '-210' to each side of the equation. 210 + -210 + -28p = -210 + -210 Combine like terms: 210 + -210 = 0 0 + -28p = -210 + -210 -28p = -210 + -210 Combine like terms: -210 + -210 = -420 -28p = -420 Divide each side by '-28'. p = 15 Simplifying p = 15
| p+p(2/3)+p(1/2)=234 | | 1/4t+9=5 | | 10(32-y)=6y | | 4x*4x-21x+39=3x+4 | | 3+4n=8n-9 | | 10-2(3x+2)=11 | | 76=14 | | -10q=10-9q | | 2z-4-z= | | 7(n)=48 | | 5/6y=-8/9 | | 108z=24(z+7) | | 3a+6=12 | | 7x-2=21 | | 8y-7(y+3)=14-8 | | 2c-4-3c= | | n/4-8=15 | | 8+3y=18 | | 1-5n+6=-13 | | 15w-3(4w-6)=3w+9-9w | | 2d=a-b | | 7x-71=54+2x | | 2/3x+19=49 | | 7+1=27/10 | | 6x*6x+11x-72=0 | | 1+5x+4x=-17 | | 26-12x=98 | | y+1=27/10 | | 16+y-11=18-5 | | 3p+7=103 | | 5(-2x+7)+2=12 | | 2z-5z=-5 |